School Evaluation Model of Writing Skills - Rodríguez Fuentes, Antonio; Gallego Ortega, José Luis; Figueroa Sepúlveda, Susana (Rastros Rostros, 2017)
Introduction: The article presents a form of writing evaluation for students of compulsory (and post-compulsory) elementary education and other non-school educational institutions that pursue such objective. This is not related to any specific subject or curricular area as they are cross-sectional transdisciplinary skills.As a theoretical reference of the activity to be evaluated, writing, the Flower and Hayes’s model, as qualified by Hayes, has been used, which describes these skills as an eminently cognitive exercise involving four phases or processes simultaneously and recursively: planning of the text mentally or design of the draft, itstranscription in a given format through a conventional language, review of the result from various dimensions and according to the plan, and self-regulation of the whole process.Materials and methods:This complex evaluation is approached through a mixed model of basically qualitative research, using content analysis, but with analytical details of a descriptive and inferential quantitative analysis. Results: A guide questionnaire is employed for the clinical-cognitive interview according to the cognitive nature of the activity and data are extracted to calculate the progression of the activity from one course to another. Conclusions: In previous pilot studies, certain evolution of writing has been determined from the evidence, but not in all courses or dimensions and, thus, not as expected.
Keywords: writing acquisition; writing development; writing evaluation; writing